The physics of fun - Mooney, Carla, 1970- (Inquire and investigate., 2021)
Provides middle schoolers with a full-color introduction to physics that explores the forces, motion, energy, sound and light waves, and electricity behind fun activities in the real world. Includes hands-on STEM activities, color photographs, a glossary, sidebars, fact boxes, critical thinking questions, a timeline, and further resources.